Errors in Descriptive Essay Text for Fifth-Grade Elementary School Students - Abdurahim, Antasary; Santoso, Anang; Harsiati, Titik (Universitas Pendidikan Ganesha, 2023)
Writing activities make students active in learning and stimulate the ability to put words together. However, teachers need help guiding students in learning to write. This research analyzes errors in the descriptive text of fifth-grade elementary school students. This type of research is qualitative descriptive research. The research design used is a qualitative descriptive design. The population in this study was 20 fifth-grade students at an elementary school. This research data collection method uses document recording. The research instrument used in this research is documentation notes. The data analysis technique used is descriptive qualitative. The research results showed 14 errors in word formation (morphology), including one error in the prefix, five errors in using the di- form, and one in reduplication. Sentence (syntax) errors totaled 15, including sentences without a subject totaling five errors, doubling the subject amounting to one error, illogical sentences totaling three errors, ambiguous sentences or ambiguous sentences totaling two errors, deletion of conjunctions totaling one error, sentence order incorrectly logically amounted to one error, and sentences influenced by foreign language structures amounted to one error. There were 25 spelling errors, including four errors in the use of capital letters in the title of the essay, nine errors in the use of capital letters at the beginning of sentences, eight errors in the use of capital letters in the middle of sentences, and four errors in the use of abbreviations and acronyms.